Enhanced the photocatalytic activity of Ni-doped ZnO thin films: Morphological, optical and XPS analysis. (June 2016) - Abdel-wahab, M.Sh.; Jilani, Asim; Yahia, I.S.; Al-Ghamdi, Attieh A.
Abstract: Pure and Ni-doped ZnO thin films with different concentration of Ni (3.5 wt%, 5 wt%, 7 wt%) were prepared by DC/RF magnetron sputtering technique. The X-rays diffraction pattern showed the polycrystalline nature of pure and Ni-doped ZnO thin films. The surface morphology of pure and Ni doped ZnO thin films were investigated through atomic force microscope, which indicated the increase in the grain dimension and surface roughness with increasing the Ni doping. The UV–Visible transmission spectra showed the decrease in the transmittance of doped ZnO thin films with the incorporation of Ni dopants. The surface and chemical state analysis of pure and Ni doped ZnO thin films were investigated by X-rays photoelectron spectroscopy (XPS). The photocatalytic activities were evaluated by an aqueous solution of methyl green dye. The tungsten lamp of 500 W was used as a source of visible light for photocatalytic study. The degradation results showed that the Ni-doped ZnO thin films exhibit highly enhanced photocatalytic activity as compared to the pure ZnO thin films. The enhanced photocatalytic activities of Ni-doped ZnO thin films were attributed to the enhanced surface area (surface defects), surface roughness and decreasing the band gap of Ni-doped ZnO thin films. Our work supports the applications of thin film metal oxides in waste water treatment. Graphical abstract: Highlights: Pure and Ni doped ZnO thin films were deposited using DC/RF sputtering technique. Chemical state analysis of Ni doped ZnO thin films were investigated using X-rays photoelectron spectroscopy. Effect of Ni-doping on photocatalytic degradation of Methyl green dye under visible light was studied. The deposited films are efficient and possess high photo-catalytic activity.